Using mathematical criteria of evaluation for diagnostics results of cadets' training in affective sphere - S.V. Palevych; О.G. Poddubny; О.А. Tkachuk; Z.O. Tzymbaliuk (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
Objective: substantiation of the expediency of using mathematical evaluation criteria for determining the means of diagnosing a set of knowledge, skills and other competences acquired during the training of military men in the emotional (affective) sphere. Material: the study was attended by 67 cadets of the Air Force University, who are not the pilots and are at the 3rd year of study. For assessing the ability to manage their behavior through management of emotions, a technique of studying the emotional intelligence of military personnel at different stages of training and physical tests are  related to overcoming objective and subjective obstacles. For the processing of the results was used the method of correlation, discriminant analysis and decision tree methods for the classification problem. The significance level for all statistics was established at p <0.05. Results: A positive linear relationship between the levels of performance of special exercises and the level of emotional stability were established. The models of discriminant analysis and the rule of classification of the recognition of the level of emotional stability according special physical preparedness level are determined. It was established that exercises in the obstacles course and turns in the gymnastics wheel are the main variables that allow classifying the students according to the level of emotional stability. Conclusions: The using of mathematical criteria for evaluating the results of the implementation of special exercises can differentiate according to the objective characteristics of cadets in category and simplifies the methodological work on recognition in the dynamics of physical improvement of military personnel, a local assessment of emotional and volitional resistance to the negative impact of the factors of modern combat.